EFEKTIVITAS KOMUNIKASI PEMASARAN TERHADAP MINAT JAMU TRADISIONAL PADA GENERASI Z BALONGSARI - Shalehah, Yushinta Alifatus (Sintesa, 2025)
Traditional herbal medicine is a cultural heritage product of Indonesia that is currently experiencing a decline in interest, particularly among Generation Z. This study aims to analyze the effectiveness of marketing communication on the interest of Generation Z consumers in traditional herbal medicine in Balongsari Subdistrict, Surabaya. The theories used are the Marketing Communication Mix and the Theory of Planned Behavior (TPB) to understand the factors influencing consumer interest. This research employs a descriptive quantitative approach by collecting data through questionnaires, followed by data analysis using SPSS with simple linear regression tests, t-tests, and Friedman tests. The results show that the effectiveness of marketing communication has a positive and significant influence on consumer interest, as indicated by the t-value being greater than the t-table value. It can be concluded that an increase in the Effectiveness of Marketing Communication (X) will help increase consumer interest (Y) among Generation Z in traditional herbal medicine products. In this study, effective marketing communication strategies can have a positive impact in attracting the attention and interest of Generation Z consumers towards traditional herbal medicine in Balongsari Subdistrict, Surabaya. Keywords: Effectiveness of Marketing Communication, Consumer Interest, Traditional Herbal Medicine, Generation Z.